Accuracy of genotype MTBDRplus line probe assay in patients with tuberculous pleural effusion: comparison with clinical and culture based diagnosis. Issue 4 (2nd April 2020) - Irfan, Muhammad; Idrees, Farah; Jabeen, Kauser; Zubairi, Ali Bin Sarwar; Butt, Sehrish; Hasan, Rumina
Abstract: Background: Pleural tuberculosis (TB) diagnosis is challenging due to paucibacillary disease. Diagnostic accuracy of GenoType MTBDR plus Line Probe Assay (MTBDRplus) has been evaluated in this study for pleural TB diagnosis. Objective: To evaluate diagnostic accuracy of MTBDRplus for pleural TB diagnosis compared to clinical and microbiological diagnosis. Methods: This prospective study was conducted at the Aga Khan University, Pakistan. Pleural fluid from 203 suspected pleural TB patients was collected and tested for smear, culture and MTBDRplus. Diagnostic accuracy of MTBDRplus was determined using clinical diagnosis and culture as the gold standard. Results: Out of 203 TB suspect patients, MTBDRplus, culture and smear were positive in 14 (6. 9%), 27 (13.3%) and 4 (1.9%) cases, respectively. A total of 106/203 patients (27 culture positive and 79 culture negative) successfully completed TB treatment. Considering clinical diagnosis as gold standard, sensitivity of MTBDRplus was 13.2%; 95% CI (7.4–21.2%) and specificity was 100%; 95% CI (96.1–100%). The sensitivity and specificity of MTBDRplus in culture positive samples were 44.4%; 95% CI (25.5–64.7%) and 98.9%; 95% CI (95.9–99.9%), respectively. Excluding indeterminate results, MTBDRplus accurately detected isoniazid sensitivity in 5/6 and rifampicin sensitivity in 6/6 cases. Conclusion: MTBDRplus had a low sensitivity of 13.2% in clinically diagnosed and 44% in culture-confirmed pleural TB patients and therefore could not be included in most diagnostic algorithms. Due to a higher sensitivity than smear, MTBDRplus may have a role in tuberculous pleural effusion diagnosis if it is positive pending culture results and pleural biopsy.